Importance of Corneal Angiography in Subclinical Limbitis in a Case of Atopic Keratoconjunctivitis - Romano, Davide; Coco, Giulia; Borgia, Alfredo; Kaye, Stephen B; Romano, Vito (Cornea, 2022)
The aim of this study was to report corneal angiography features in subclinical limbitis in a patient with atopic keratoconjunctivitis.PURPOSEThe aim of this study was to report corneal angiography features in subclinical limbitis in a patient with atopic keratoconjunctivitis.This is a case report.METHODSThis is a case report.A 22-year-old woman with a medical history of atopic keratoconjunctivitis was referred for bilateral corneal neovascularization with scarring. On examination, no signs of active disease were noticed at the slit lamp. Ocular surface angiography detected active corneal limbitis, showing as limbal leakage at fluorescein angiography in the early phase and leakage after indocyanine green angiography in the late phase. The patient was treated with topical corticosteroid. At follow-up, the fluorescein angiography and indocyanine green angiography no longer showed limbal leakage, whereas the slit lamp examination was unchanged.RESULTSA 22-year-old woman with a medical history of atopic keratoconjunctivitis was referred for bilateral corneal neovascularization with scarring. On examination, no signs of active disease were noticed at the slit lamp. Ocular surface angiography detected active corneal limbitis, showing as limbal leakage at fluorescein angiography in the early phase and leakage after indocyanine green angiography in the late phase. The patient was treated with topical corticosteroid. At follow-up, the fluorescein angiography and indocyanine green angiography no longer showed limbal leakage, whereas the slit lamp examination was unchanged.Active allergic corneal limbitis may present as subclinical inflammation, with no signs of activity at the slit lamp examination. Therefore, its diagnosis can be challenging without the use of corneal angiography.CONCLUSIONSActive allergic corneal limbitis may present as subclinical inflammation, with no signs of activity at the slit lamp examination. Therefore, its diagnosis can be challenging without the use of corneal angiography.